2023
DOI: 10.1101/2023.11.13.566806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovering cryptic pocket opening and binding of a stimulant derivative in a vestibular site of the 5-HT3Areceptor

Nandan Haloi,
Emelia Karlsson,
Marc Delarue
et al.

Abstract: Ligand-gated ion channels propagate electrochemical signals in the nervous system by opening ion-selective pores in response to neurotransmitter release. A diverse set of allosteric modulators including neurosteroids, anesthetics, and lipids modulate their function in myriad ways, suggesting a complex conformational landscape. However, structures of ligand-bound ion-channel complexes can be difficult to capture by experimental techniques like cryogenic electron microscopy, particularly when binding is dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 66 publications
2
2
0
Order By: Relevance
“…In parallel with the present study, we have observed BrAmp in particular to potentiate 5-HT 3A Rs even more potently than sTeLIC [28]. Furthermore, BrAmp modulation of 5-HT 3A Rs is sensitive to mutations at positions equivalent to sTeLIC b4-W75, b5-L93, and b6-Y104, and appears to require a similar rearrangement of the b4 residue out of the vestibular site and into contact with the complementary b5 [28]. Taken together, these findings support a general mechanism of pocket opening and ligand modulation in a subset of pLGICs including mammalian 5-HT 3A Rs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In parallel with the present study, we have observed BrAmp in particular to potentiate 5-HT 3A Rs even more potently than sTeLIC [28]. Furthermore, BrAmp modulation of 5-HT 3A Rs is sensitive to mutations at positions equivalent to sTeLIC b4-W75, b5-L93, and b6-Y104, and appears to require a similar rearrangement of the b4 residue out of the vestibular site and into contact with the complementary b5 [28]. Taken together, these findings support a general mechanism of pocket opening and ligand modulation in a subset of pLGICs including mammalian 5-HT 3A Rs.…”
Section: Discussionsupporting
confidence: 89%
“…Their work further demonstrates that covalent labeling in the vestibular site modifies 5-HT 3A R currents, supporting a functional role in receptor modulation [19]. In parallel with the present study, we have observed BrAmp in particular to potentiate 5-HT 3A Rs even more potently than sTeLIC [28]. Furthermore, BrAmp modulation of 5-HT 3A Rs is sensitive to mutations at positions equivalent to sTeLIC b4-W75, b5-L93, and b6-Y104, and appears to require a similar rearrangement of the b4 residue out of the vestibular site and into contact with the complementary b5 [28].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations